Pengembangan E-Modul Sistem Koloid Berbasis Guided Discovery Learning Untuk Siswa Kelas XI SMA - Fadila Maharani; Yerimadesi Yerimadesi (Edukimia, 2022)
The 2013 curriculum requires students to actively participate and be skilled within the use of knowledge and communication technology in the learning method so that learning is more interactive, efficient and effective. One of them is the use of e-modules or electronic teaching materials. This study aims to determine the validity, practicality, and effectiveness of the development of Guided Discovery Learning-based colloid system e-module for class XI grade senior high school students. This form of study is educational design research that makes use of the Plomp model. The validity check turned into completed with the aid of using five validators consisting of two chemistry lecturers at a university in the city of Padang and three chemistry teachers at a high school in Padang Pariaman district. The practicality and effectiveness test was conducted on three chemistry teachers and students of class XII MIPA at one of the high schools in Padang Pariaman district. The outcomes of validity and practicality had been analysed by the usage of the Aiken V formula and results of the effectiveness of e-module data using N-Gain formula. The conclusion of this research is that the e-module colloid system based on Guided Discovery Learning for class XI SMA which was developed is valid, practical, and effectively used to improve students understanding of concepts.